Reporting of Banking Cash Transactions to Prevent Corruption Crimes Reviewed from Law Number 8 of 2010 - Malue, Kathryin (Jurnal Multidisiplin Indonesia, 2025)
Corruption is a serious threat to economic stability and government integrity, where cash transactions in the banking system are often used as a means of laundering money proceeds from crime. This study aims to analyze the regulation of cash transaction reporting in banking to prevent corruption and identify preventive measures. This study highlights and analyzes the implementation of Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes in the context of banking transactions. This study uses a normative juridical method with a literature approach, which examines primary and secondary legal materials to identify the effectiveness of banking regulations in preventing corruption. The results of the study show that the mechanism for reporting cash transactions by banks has been strictly regulated through PPATK, but there are still gaps in its implementation that allow corruption to still occur. The conclusion of this study emphasizes the importance of strengthening regulations and supervision of financial transactions, limiting the nominal amount of cash transactions, as well as more effective coordination between banking authorities and law enforcement agencies in eradicating corruption through the banking system. With stricter supervision, the transparency of financial transactions can be improved, thereby preventing the use of banking institutions as a means of laundering money from corruption.